THE ROLE OF THE SCHOOL PRINCIPLE AS SUPERVISOR IN BECKING A PROFESSIONAL TEACHER - Pratiwi, Ela Trisna (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The study aims to analyze how the educational supervision techniques applied by madrasah heads in making professional teachers in MAN 1 Probolinggo City. This research uses a descriptive qualitative approach. Data collection techniques use interview, observation and documentation techniques. The results showed that the educational supervision techniques applied by the head of the madrasa in making teachers professional, firstly applying individual supervision techniques, secondly group supervision techniques Keywords: Supervision, Individual, Group